Common Sense Beliefs about the Central Self, Moral Character, and the Brain - Fernandez-Duque, Diego; Schwartz, Barry (Frontiers in Psychology, 2016)
To assess lay beliefs about self and brain, we probed people's opinions about the central self, in relation to morality, willful control, and brain relevance. In study 1, 172 participants compared the central self to the peripheral self. The central self, construed at this abstract level, was seen as more brain-based than the peripheral self, less changeable through willful control, and yet more indicative of moral character. In study 2, 210 participants described 18 specific personality traits on 6 dimensions: centrality to self, moral relevance, willful control, brain dependence, temporal stability, and desirability. Consistent with Study 1, centrality to the self, construed at this more concrete level, was positively correlated to brain dependence. Centrality to the self was also correlated to desirability and temporal stability, but not to morality or willful control. We discuss differences and similarities between abstract (Study 1) and concrete (Study 2) levels of construal of the central self, and conclude that in contemporary American society people readily embrace the brain as the underlying substrate of who they truly are.